Creating Competitive Advantage Through Strategic Social Entrepreneurship In The Non-Profit Sector - Ni Luh Sudianti; I Nengah Dasi Astawa (Jurnal Manajemen dan Bisnis, 2016)
profits organizations create a competitive advantage in order struggle to gainfinancial sustainability. Widhya Asih Bali Foundation sits under service for children andcommunity self-help assistance to empower Bali’s otherwise overlooked children, givingthem a chance at the kind of life that most people around the world take for granted. Settingup entrepreneurial mindset toward the entrepreneurial activities. Widhya Assih BaliFoundation is strengthening internal methods of generating financial sustainability of publicprograms. The focus of this study in social entrepreneurship is geared toward the internalcompetitive nature of how the organization operates in building impact through the children.Though it may be worth considering how existing resources can also meet external needs thatcan add value in society through commerce (business) internal generating money makingmethods. Such an approach does not have to be geared toward cost-cutting services rather itcan be toward providing a unique service and/or product. In this way a competitiveadvantage can be achieved for financial gain within the organization for future program andorphan sponsorship.Keywords: Competitive Advantage, Generic Strategy, Social Entrepreneurship